2006
DOI: 10.1111/j.1463-6395.2006.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological variation along and ultrastructural organization of the epithelium of the ductus epididymidis of the fan‐throated lizard Sitana ponticeriana Cuvier

Abstract:  Abstract Akbarsha, M.A., Kadalmani, B. and Tamilarasan, V. 2006. Histological variation along and ultrastructural organization of the epithelium of the ductus epididymidis of the fan-throated lizard Sitana ponticeriana Cuvier. -Acta Zoologica (Stockholm) 87 : 181-196The epididymis of the fan-throated lizard Sitana ponticeriana was subjected to light and transmission electron microscopic analysis to find the histological variation along the ductus epididymidis, describe the various cell types in the epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 50 publications
1
21
1
Order By: Relevance
“…A single tubule emerges from the external tunic of the testes, signifying the extra-testicular rete testis as described by Sever (2010) in his synonomizing of the terminology for reptiles. Although the number of extratesticular rete tubules varies (Table 1), the presence of a single rete testis tubule in H. turcicus is the same as in a diverse assemblage of lizards: Sitana ponticeriana (Akbarsha et al, 2006a), Eumeces fasciatus, (Reynolds, 1943), Lacerta vivipara (Martin-Saint-Ange, 1854), and Sceloporus undulatus (Forbes, 1941). Thus, this character may not have any phyletic significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A single tubule emerges from the external tunic of the testes, signifying the extra-testicular rete testis as described by Sever (2010) in his synonomizing of the terminology for reptiles. Although the number of extratesticular rete tubules varies (Table 1), the presence of a single rete testis tubule in H. turcicus is the same as in a diverse assemblage of lizards: Sitana ponticeriana (Akbarsha et al, 2006a), Eumeces fasciatus, (Reynolds, 1943), Lacerta vivipara (Martin-Saint-Ange, 1854), and Sceloporus undulatus (Forbes, 1941). Thus, this character may not have any phyletic significance.…”
Section: Discussionmentioning
confidence: 99%
“…Akbarsha et al (2006a) correctly identified these halo cells as intraepithelial leukocytes, and Hermo and Robaire (2002) consider these leukocytes are either monocytes or T lymphocytes. We are unaware of other reports of intraepithelial leukocytes in the rete testis of vertebrates, and we did not encounter these cells in the ductuli efferentes or epididymis of H. turcicus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spermatogenic activities leading to spermiation and mating behavior were the main emphasis in these investigations (Flemming, 1993;Gribbins et al, 2011;Nkosi et al, 2004;Ramírez-Bautista et al, 1996). In addition, some of the morphological studies have attempted to link specific features related to testicular activities such as the development of specific histological and ultrastructural features of the testicular tissues (including germ cells, Sertoli and Leydig cells) in relation to the seasonal activities (Akbarsha et al, 2006;Rheubert et al, 2009;Prasad, 1966, 1967). Other studies emphasized the relationship between plasma steroid concentrations and testicular activities such as spermiation relative to courtship and mating behavior (Amey and Whittier, 2000;Ando et al, 1990Ando et al, , 1992Johnson et al, 2011;Radder et al, 2001;Schuett et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant cell type in the reptilian epididymis, accounting for > 80% of the epithelium, is variously identified as a principal (Akbarsha et al, 2006a), vesicular (Holmes & Gist, 2004), columnar (Guerrero et al, 2004), or secretory cell (Desantis, Labate, M., Labate, G., & Cirillo, 2002). The shape of principal cells changes from columnar in the caput epididymis to cuboidal distally; they possess microvilli and appear to have tight junctions.…”
Section: Ductus Epididymismentioning
confidence: 99%